Photocuring 3D printing transparent conductive hydrogel and preparation method thereof
By using dopamine and pyrrole to generate nanodot combined gelatin in 3D printed hydrogels, the shortcomings of existing hydrogels in printing accuracy, mechanical strength, conductivity and transparency are solved, and high efficiency and low cost are achieved Transparent conductive hydrogel preparation, suitable for flexible electronic and wearable sensors.
Patent Information
- Application Number
- CN202411672285.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-14
AI Technical Summary
Existing 3D printed hydrogels cannot take into account both printing accuracy, mechanical strength, conductivity and transparency, resulting in low printing accuracy, easy model collapse and poor conductivity.
By dissolving dopamine and pyrrole in the acid solution, adding oxidizing agent to produce PDA-PPY powder, and decomposing it into nanodots under the action of a pro-decomposition agent, combining methacrylate gelatin and photocrosslinking agent, transparent conductive hydrogel was prepared to prepare a .
It achieves high transparency, excellent conductivity, good mechanical properties and biocompatibility, solves the shortcomings of traditional hydrogels in 3D printing, and is suitable for flexible electronic devices and wearable sensors.
Smart Images

Figure CN119431827A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of conductive hydrogels, and in particular to a photocurable 3D printed transparent conductive hydrogel and a preparation method thereof. Background Art
[0002] Hydrogel is a polymer with a large number of hydrophilic groups in the main chain or side chain and a significant three-dimensional network structure. It is widely used in the fields of medicine, chemical industry, gardening, textile, building materials and food due to its outstanding characteristics such as versatility of preparation, good biocompatibility and similarity with natural extracellular matrix. As people's lives gradually develop towards digitalization, the development of flexible electronic devices has attracted attention. Therefore, conductive hydrogel, as a unique flexible material, combines the three-dimensional micro-nano structure of gel with the electrical and optical characteristics of semiconductors. Conductive hydrogel can convert external stimuli into changes in its own electrical properties, and then output them through changes in electrical signals. The spatial network structure of the internal conductive micro-nano structure is conducive to the movement of charge carriers. Coupled with its own good bioaffinity, conductive hydrogel has gradually become the "protagonist" of flexible electronic devices and has attracted much attention.
[0003] However, traditional hydrogel molding is generally done in molds or by subtractive manufacturing technology. This method is not only very consuming and has an uncontrollable internal structure, but is also only suitable for large-scale production and not for "small and beautiful" customized manufacturing.
[0004] Compared with the traditional preparation method, after the hydrogel is combined with 3D printing technology, the hydrogel molding not only meets the controllable internal structure and personalized morphology design, but also has more diversified shapes and lower consumption costs. For the material used to prepare 3D printed hydrogel, the most widely used one is methacrylated gelatin (Gelma), and its 3D printing method is mainly photocuring 3D printing technology. However, due to its limited photocuring rate, the solid-liquid separation cannot be rapid during the photocuring process, resulting in low printing accuracy or even printing failure; at the same time, due to its low mechanical strength, the 3D printed model is easy to collapse and then cause printing failure; and the hydrogel modified by Gelma conductivity is usually opaque, for example, some black hydrogels are formed by doping conductive PPY particles in the hydrogel substrate, and using it as a dressing is not conducive to observing the healing of the wound. Therefore, the modification of Gelma and the design of hydrogels that can be used for photocuring 3D printing, which have flexibility, mechanical strength, conductivity and biocompatibility, are of great significance in the field of gel dressings or customized wearable sensors. Summary of the invention
[0005] The purpose of the present invention is to overcome the above-mentioned technical deficiencies, provide a photocurable 3D printed transparent conductive hydrogel and a preparation method thereof, and solve the technical problem that the 3D printed hydrogel in the prior art cannot take into account the printing accuracy, mechanical strength, conductivity and transparency.
[0006] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In a first aspect, the present invention provides a method for preparing a photocurable 3D printed transparent conductive hydrogel, comprising the following steps: (1) dissolving dopamine and pyrrole in a first acid solution to obtain a mixed solution; adding an oxidant solution to the mixed solution to react and generate a precipitate, which is then post-treated to obtain a PDA-PPY powder; (2) PDA-PPY powder is prepared into a dispersion liquid, and a decomposition promoter is added to react to obtain a PDA-PPY decomposition liquid; (3) Add methacrylated gelatin powder to the decomposition solution of PDA-PPY, add a photocrosslinker after dissolving, and mix well to obtain a hydrogel precursor; the hydrogel precursor is 3D printed and photocured to obtain a transparent conductive hydrogel.
[0007] In a second aspect, the present invention provides a photocurable 3D printed transparent conductive hydrogel prepared by the above preparation method.
[0008] Compared with the prior art, the beneficial effects of the present invention include: The present invention uses dopamine, pyrrole monomers and acid to form a mixed solution, and the acid can prevent dopamine from oxidizing and self-polymerizing in advance; then, an oxidant is used to promote the oxidative polymerization of dopamine and pyrrole groups to obtain PDA-PPY; then, under the action of a decomposition promoter, PDA-PPY is decomposed from a large group into nanodots (NDs), and then the decomposition product is added to gelatin, so that the PDA-PPY nanodots are fully dispersed in the hydrogel and retain good light transmittance, which not only provides conductive particles for the hydrogel, but also significantly improves the conductivity of the hydrogel and improves the mechanical properties of the hydrogel. The preparation process of the transparent conductive hydrogel of the present invention is simple, low-cost, and highly repeatable. The cross-linking is completed in a short time by light curing, so the fidelity of the printed stent can be well achieved, and it can be used for tissue repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 The infrared spectra of PDA-PPY, PP-Gelma in Example 1 and Gelma in Comparative Example 1; Figure 2 This is the SEM of the freeze-dried PP-Gelma hydrogel in Example 1; Figure 3 The monitored resistance change rate diagram of the hydrogels in Example 1 and Comparative Example 1; Figure 4 is an optical micrograph of the hydrogel of Example 1; Figure 5 This is a 3D printed physical image of the hydrogel in Example 1; Figure 6 1 is a shear viscosity-shear rate curve of the hydrogel prepolymer solution of Example 1 and Comparative Example 1; Figure 7 is a light transmittance curve diagram of the hydrogels of Examples 1-2 and Comparative Example 1; Figure 8 This is a diagram showing the mechanism of action of the hydrogel polymerization of the present invention. DETAILED DESCRIPTION
[0010] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0011] In view of the defects of 3D printed hydrogels in the prior art that printing accuracy, mechanical strength, conductivity and transparency cannot be taken into account at the same time, the present invention provides a photocurable 3D printed transparent conductive hydrogel and a preparation method thereof. The preparation method of the present invention has the advantages of simple steps, low cost and biofriendliness. The obtained photocurable 3D printed transparent conductive hydrogel has the advantages of high transparency, excellent conductivity, good mechanical properties and high biocompatibility.
[0012] In a first aspect, the present invention provides a method for preparing a photocurable 3D printed transparent conductive hydrogel, comprising the following steps: (1) dissolving dopamine and pyrrole in a first acid solution to obtain a mixed solution; adding an oxidant solution to the mixed solution to react and generate a precipitate, which is then post-treated to obtain a PDA-PPY powder; (2) PDA-PPY powder is prepared into a dispersion liquid, and a decomposition promoter is added to react to obtain a PDA-PPY decomposition liquid; (3) Adding methacrylated gelatin powder to the decomposition solution of PDA-PPY, adding a photocrosslinking agent after dissolution, and mixing evenly to obtain a hydrogel precursor; the hydrogel precursor is used as a 3D printing ink, and subjected to 3D printing and photocuring to obtain a transparent conductive hydrogel.
[0013] Preferably, in step (1), the ratio of dopamine to pyrrole is (0.1-0.3) g: 0.12 mL. Insufficient dopamine will reduce the water solubility of the synthesized PDA-PPY powder, while excessive dopamine will reduce the conductivity.
[0014] Preferably, in step (1), the preparation process of the mixed solution specifically comprises: dissolving dopamine powder in a first acid solution in an ice water bath at 0 to 10° C., then adding pyrrole, and stirring at a speed of 50 to 200 rpm to completely dissolve it to obtain a mixed solution.
[0015] Preferably, in step (1), the first acid solution comprises a hydrochloric acid solution with a concentration of 0.5 to 3 mol / L; and the ratio between dopamine and the first acid solution is (0.025 to 0.3) g: 20 mL.
[0016] Preferably, in step (1), the mass ratio of dopamine to oxidant is (0.025-0.3): (0.2-0.5).
[0017] Preferably, in step (1), the oxidant solution is an acidified ferric salt solution; the acidified ferric salt solution is obtained by dissolving an iron salt in a second acid solution; the iron salt includes anhydrous ferric chloride, and the second acid solution includes a hydrochloric acid solution with a concentration of 0.5 to 3 mol / L; the ratio between the iron salt and the second acid solution is (0.2 to 0.6) g: 5 mL.
[0018] Preferably, in step (1), the reaction is carried out in an ice-water bath at 0 to 10° C. and stirred for 9 to 12 hours.
[0019] Preferably, in step (1), the post-treatment includes centrifugal washing and freeze-drying; the rotation speed in the centrifugal washing is 12000-17000 rpm, and the number of centrifugation is 3-6 times.
[0020] Preferably, in step (2), the concentration of PDA-PPY in the dispersion is 0.1 to 0.6 mg / mL.
[0021] Preferably, in step (2), the decomposition promoter includes ammonium persulfate; and the mass ratio of the PDA-PPY powder to the decomposition promoter is 1:(10-30).
[0022] Preferably, in step (2), the reaction conditions after adding the decomposition promoting agent are: stirring at a rotation speed of 50 to 200 rpm for 10 to 24 hours.
[0023] Preferably, in step (3), the preparation step of methacrylated gelatin comprises: Gelatin is dissolved in 0.2-0.3 mol / L carbonate buffer, methacrylic anhydride is added dropwise to react, the pH value of the reaction solution is adjusted to 7.2-7.8 with hydrochloric acid to stop the reaction, and finally methacrylic acid acylated gelatin is obtained by dialysis and freeze drying.
[0024] Further preferably, the ratio between gelatin and carbonate buffer is (15-25) g: 200 mL; the ratio between gelatin and methacrylic anhydride is (15-25) g: 2 mL; the reaction is stirred at 40-60° C. for 2-4 hours, and then hydrochloric acid is added to adjust the pH value of the reaction solution to 7.2-7.8.
[0025] Preferably, in step (3), the grafting rate of methacrylic anhydride in methacrylated gelatin is 70-90%; the ratio of methacrylated gelatin to the decomposition liquid of PDA-PPY is (0.1-0.5) mg:1 mL. The amount of PDA-PPY nanoparticles in gelatin is controlled by controlling the concentration of PDA-PPY in the dispersion liquid of step (2) and the volume of the decomposition liquid of PDA-PPY. Too little amount of PDA-PPY nanoparticles is not conducive to improving the conductivity of the obtained hydrogel, and too much amount will reduce the transmittance of the hydrogel.
[0026] Preferably, in step (3), the mass ratio of methacrylated gelatin to the photocrosslinking agent is (1-5):100; the photocrosslinking agent includes lithium phenyl-2,4,6-trimethylbenzoylphosphinate or 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (I2959).
[0027] Preferably, in step (3), the conditions for dissolving the methacrylated gelatin are: stirring at 35-45°C and 50-200 rpm for 1-2 hours; and the conditions for uniform mixing after adding the photocrosslinking agent are: stirring at 35-45°C for 0.5-2 hours.
[0028] Preferably, in step (3), the 3D printing conditions include: a printing speed of 6 to 10 mm / s, a printing pressure of 0.15 to 0.25 MPa, a printing spacing of 1.2 to 1.8 mm, and a barrel temperature of 10 to 18°C.
[0029] Preferably, in step (3), the conditions for light curing include: UV lamp wavelength 365nm, light power 400-800mw / cm 2 , the illumination time is 1 to 3 seconds.
[0030] In a second aspect, the present invention provides a photocurable 3D printed transparent conductive hydrogel prepared by the above preparation method.
[0031] See also Figure 8 , the main mechanism of action and advantages of the present invention: (1) The present invention uses dopamine, pyrrole monomers and acid solution to jointly construct a mixed liquid system, and prevents dopamine from premature oxidation and self-polymerization in an acid solution (preferably hydrochloric acid); then slowly add an acidified iron salt solution as an oxidant in a low temperature environment, and stir rapidly at the same time. In this process, low temperature treatment can make the polymerized PDA-PPY particle size small, and add an acidified ferric chloride solution to introduce trivalent iron ions into the solution. The strong oxidizing property of trivalent iron ions promotes the oxidative polymerization of dopamine and pyrrole groups. At the same time, rapid stirring promotes the contact between dopamine and pyrrole, thereby reducing the products of self-polymerization of the two.
[0032] (2) Ammonium persulfate is used as a decomposition promoter to promote the decomposition of PDA-PPY from large groups into nanodots (NDs). Therefore, the decomposition products are added to gelatin to make the PDA-PPY nanodots fully dispersed in the hydrogel. This not only provides conductive particles for the hydrogel, significantly improving the conductivity of the hydrogel, but also improves the mechanical properties of the hydrogel.
[0033] (3) The preparation process of the transparent conductive hydrogel of the present invention is simple, low-cost, and highly repeatable. It does not require the multi-layer assembly process of the traditional device substrate layer, conductive layer, etc. It can be directly connected to the circuit for use, and does not require expensive equipment and a special preparation environment. The reaction conditions in the preparation method are mild, and the required conditions are not harsh; photocuring completes cross-linking in a short time, so the fidelity of the printed scaffold can be better achieved, and it can be used for tissue repair. The excellent performance of the Gelma scaffold material itself is fully demonstrated, with good biocompatibility, good cell adhesion and other characteristics. Compared with other materials, the scaffold material design is simple, the material shape and microstructure are controllable, the mechanical properties are good, the cost is low, and the source is wide, providing a new 3D printable scaffold material for tissue engineering research.
[0034] The present invention is further described in detail below through specific examples. Among them, all raw materials are commercially available, and the photocrosslinker is I2959, which is from Shanghai Aladdin Biochemical Technology Co., Ltd. (Aladdin), with a purity of ≥98.0%; the preparation steps of methacrylated gelatin include: dissolving gelatin (purchased from Sigma, derived from pig skin) in 0.25 mol / L carbonate buffer, then dropping methacrylic anhydride (MAA, purchased from Aladdin, with a purity of ≥94%, containing 0.2% topanol stabilizer), reacting at 50°C for 1.5 hours, then adjusting the pH value of the reaction solution to 7.2-7.8 with hydrochloric acid to stop the reaction, and finally dialyzing and freeze-drying to obtain methacrylated gelatin; wherein, the ratio between gelatin and carbonate buffer is 20 g: 200 mL; the ratio between gelatin and methacrylic anhydride is 20 g: 2 mL; the grafting rate of methacrylic anhydride in the obtained methacrylated gelatin is about 80%.
[0035] Example 1 (1) Weigh 0.2 g (1.3 mmol) of dopamine powder and dissolve it in 20 mL of 1 mol / L hydrochloric acid solution. Then add 0.12 mL of pure pyrrole liquid to the solution and stir at 100 rpm in an ice water bath to completely dissolve the mixture to obtain a mixed solution. Weigh 0.4 g of anhydrous ferric chloride and dissolve it in 5 mL of 1 mol / L hydrochloric acid solution to prepare an acidified ferric chloride solution; The acidified ferric chloride solution was added to the mixed solution, and the mixture was stirred for 10 hours under an ice-water bath, and then the reaction was stopped. After centrifugation and washing for 5 times at 15000 rpm, the supernatant was removed, and the obtained black precipitate was freeze-dried to obtain a black solid, which was polypyrrole loaded with polydopamine, denoted as PDA-PPY.
[0036] (2) Weigh 2 mg of PDA-PPY powder and disperse it in 10 mL of pure water. After stirring at 100 rpm for complete dispersion, add 35 mg of ammonium persulfate powder and stir at 100 rpm for 12 h to obtain the decomposition solution of PDA-PPY. (3) Weigh 2 mg of Gelma powder, stir and dissolve it in the decomposition solution of PDA-PPY at 100 rpm, then add 0.1 g of I2959, and ultrasonically stir the resulting mixture at 45 °C for 2 h to completely dissolve it. Transfer the mixture to the barrel of the 3D printer, set the model parameters and printing spacing, and adjust the printing speed and printing pressure to make the nozzle filament continuous and uniform. The specific printing parameters are: printing speed at 8 mm / s, printing pressure at 0.2 MPa, printing spacing at 1.5 mm, and barrel temperature at 14 °C; and obtain a transparent conductive hydrogel under light curing, which is recorded as PP-Gelma. Place the printed model in PBS buffer and store it in a refrigerator at 4 °C.
[0037] Example 2 The difference between Example 2 and Example 1 is that the amount of PDA-PPY weighed in step (2) is 6 mg, and the other steps and conditions are the same.
[0038] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that: Step (1) and Step (2) are not performed, and in Step (3), 2 mg of Gelma powder is directly dissolved in 10 mL of pure water, and then 0.1 g of I2959 is added and stirred to obtain a mixed solution, and 3D printing and light curing are performed under the same conditions as Example 1.
[0039] Performance Testing The hydrogels obtained in Example 1, Example 2 and Comparative Example 1 were tested, and the main test processes or conditions were as follows: (1) Scanning electron microscopy: The hydrogel prepared in Example 1 was freeze-dried using a vacuum freeze dryer. The dried sample was then mounted on a sample plate and gold sputtered. A scanning electron microscope and a field emission gun were then operated at 5 kV to observe the microstructure.
[0040] (2) Infrared spectroscopy characterization: The hydrogels prepared in Example 1 and Comparative Example 1 and the PDA-PPY sample prepared in Example 1 were freeze-dried using a vacuum freeze dryer. 1 mg of each of the dried hydrogel sample and the PDA-PPY sample was mixed with the dried potassium bromide powder and ground evenly. The powder was then placed in an infrared mold for tableting. The tablet was then placed in an infrared spectrometer and the concentration was measured at 0.48 cm. -1 The resolution of 400-4000cm was obtained by scanning -1 Spectral images within the range.
[0041] (3) Conductivity characterization: A 2 cm × 2 cm × 2 cm cube was made using Computer Aided Design software, and the model file was imported into a 3D printer. According to the model, hydrogels of 2 cm × 2 cm × 2 cm were prepared in Examples 1, 2, and Comparative Example 1, respectively. The hydrogel was placed on the platform of a four-probe resistance tester, and the conductivity of the hydrogel was automatically measured using the block resistance mode and a current of 0.1 mA.
[0042] (4) Twist resistance test: Use Computer Aided Design software to make a 10cm×2cm×2cm cuboid, import the model file into a 3D printer, and according to the model, Example 1 and Comparative Example 1 are respectively prepared into 10cm×2cm×2cm hydrogels. Place the hydrogel at the wrist joint, use conductive tape to fix the two ends of the hydrogel with a multimeter needle, and measure the resistance change at different angles by turning the wrist, with the upward turn as the acute angle and the downward turn as the blunt angle. Stay at each angle for about 10 seconds, record the meter data change, and calculate the resistance change rate.
[0043] (5) Viscosity characterization: Take 2 mL of the mixed solution obtained by adding Gelma and I2959 in step (3) of Example 1 and Comparative Example 1 as sample solution, and slowly add the sample solution into the sample tank of the viscometer to prevent the liquid from overflowing. Pay attention to the flow of the solution during the test to prevent the solution from flowing out.
[0044] (6) Light transmittance test: A 5 cm × 1 cm × 0.1 cm cuboid was made using Computer Aided Design software, and the model file was imported into a 3D printer. According to the model, hydrogels of 5 cm × 1 cm × 0.1 cm were prepared in Example 1 and Comparative Example 1, respectively. The hydrogel was placed in a cuvette, and the UV transmittance in the range of 900-200 nm was tested using a UV spectrophotometer.
[0045] (7) In vitro cytotoxicity test process of the extracted liquid: The hydrogels obtained in Example 1, Example 2 and Comparative Example 1 were cut into 12 cm 2 , soaked in 75% ethanol, dried, and sterilized by ultraviolet irradiation for 2 hours. After being fully rinsed three times with PBS buffer, the fiber membrane was immersed in the prepared 2 mL DMEM culture medium. After 24 hours, the culture medium was removed and filtered with a 0.22 μm filter to obtain the extract, which was sealed for later use. Mouse fibroblasts (NIH 3 T 3 ) After culturing to a certain density, use trypsin to digest and count the cells, prepare a certain concentration of cell solution, and use 1×10 4 The cells were inoculated in a 96-well plate at a density of 10 cells / well. After the cells were inoculated in the well plate for 24 hours, the culture medium was aspirated, and 2 mL of extract was added to start the culture. The wells with ordinary DMEM culture medium were used as the control group. The extract and culture medium were discarded after 24 hours. After washing twice with PBS, a mixture of 180 μL of culture medium and 20 μL of MTT was added to each well in the dark. After incubation at 37°C for 4 hours, the supernatant was slowly aspirated, and 150 μL of dimethyl sulfoxide (DMSO) was added to dissolve the blue-purple crystals at the bottom. The wells were placed in a shaker and shaken at low speed for 10 minutes. 100 μL of the dissolved solution was taken in a 96-well plate, and the absorbance was detected at 490 nm with an enzyme marker, the cell survival rate was calculated, and the toxicity level of the material was evaluated.
[0046] The test results are as follows: Figure 1 The infrared spectra of PDA-PPY, Example 1 and Comparative Example 1 are shown in Figure 1. The infrared spectra of PDA-PPY at 1600 cm -1 The carbonyl characteristic peaks near 1000 cm -1 The characteristic peak of carboxyl group near Gelma is at 1600cm -1 The nearby carbon group and peptide bond characteristic peaks are both shown in the infrared spectrum of PP-Gelma, proving that the two are successfully compounded together.
[0047] Figure 2This is a scanning electron microscope image of the hydrogel prepared in Example 1. The hydrogel is porous in microscopic view, and the diameter of each pore is about 100 μm. There are no obvious granular foreign matter around and inside the micropores of the hydrogel, indicating that the polypyrrole loaded with polydopamine is successfully decomposed into smaller nanodots.
[0048] Figure 3 It is a line graph of the resistance change rate of the hydrogel at different bending degrees, indicating that the hydrogel has good conductive properties and the resistance is sensitive to strain response.
[0049] Figure 4 This is an optical microscope image of the hydrogel prepared in Example 1, which shows that the hydrogel has uniform filaments and high fidelity, and can print a high-simulation model.
[0050] Figure 5 This is a physical picture of the 3D printed hydrogel prepared in Example 1, which reflects the good photocuring printing performance of the hydrogel and can print a high-precision model that is basically the same as the three-dimensional modeling size, indicating a low shrinkage rate.
[0051] Figure 6 The shear viscosity-shear rate curves of the hydrogel prepolymer solutions of Example 1 and Comparative Example 1 show that the viscosity decreases with an increase in shear rate, indicating that the material has shear thinning behavior and is suitable as a 3D printing ink. Compared with Comparative Example 1, the shear viscosity of Example 1 is significantly improved, which means that the hydrogel of the example can effectively slow down the collapse of the printed structure and has higher printing accuracy.
[0052] Figure 7 : is the light transmittance curve of the hydrogel of Example 1-2 and Comparative Example 1. Compared with Comparative Example 1, the light transmittance of Example 1-2 is slightly reduced, but still has excellent light transmittance, which is conducive to observing the recovery of the wound.
[0053] The conductivity data of the above Examples 1-2 and Comparative Example 1 are shown in Table 1, and the cytotoxicity levels are shown in Table 2.
[0054] Table 1 Conductive properties of hydrogels
[0055] As shown in Table 1, the conductivity of the hydrogel in Comparative Example 1 is the lowest, which is 1.33±0.18×10 -4 s / cm. After adding the decomposition solution of PDA-PPY, the conductivity of Example 1 was increased to 2.77±0.22×10 -3 s / cm, the conductivity of Example 2 increased by 2.83±0.15×10 -3The results show that adding PDA-PPY decomposition solution can significantly increase the conductivity of the hydrogel. This is because the PDA-PPY particles build linear channels inside the hydrogel, forming a conductive path that is conducive to the transmission of electrons.
[0056] Table 2 Cytotoxicity data of hydrogels
[0057] As can be seen from Table 2, the toxicity levels of Examples 1-2 and Comparative Example 1 are both level 0. After multiple groups of cytotoxicity experiments and analysis, the cell survival rate is above 100%, indicating that Examples 1-2 have no adverse effects on cell growth and have good biocompatibility.
[0058] The present invention provides a photocurable 3D printed transparent conductive hydrogel and a preparation method thereof, wherein dopamine and pyrrole are added to a low-temperature hydrochloric acid aqueous solution containing an oxidant, and the polypyrrole loaded with polydopamine is obtained by continuous stirring; the polypyrrole loaded with polydopamine is decomposed under the promoting decomposition effect of ammonium persulfate; methacrylated gelatin is added to the decomposition solution, stirred and dissolved, a photocrosslinking agent is added, the mixture is dissolved and mixed uniformly, and photocurable 3D printing is performed to obtain a transparent conductive hydrogel. The hydrogel printed by the present invention has high toughness, transparency, conductivity and sensing performance, and can be used for flexible customized wearable sensors.
[0059] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a photocurable 3D printed transparent conductive hydrogel, characterized in that: The steps include: (1) dissolving dopamine and pyrrole in a first acid solution to obtain a mixed solution; adding an oxidant solution to the mixed solution to react to generate a precipitate, and obtaining PDA-PPY powder through post-treatment; (2) preparing the PDA-PPY powder into a dispersion, and then adding a decomposition accelerator to react to obtain a PDA-PPY decomposition liquid; (3) Adding methacrylated gelatin powder to the decomposition solution of the PDA-PPY, adding a photocrosslinking agent after dissolution, and mixing evenly to obtain a hydrogel precursor; the hydrogel precursor is 3D printed and photocured to obtain a transparent conductive hydrogel.
2. The method for preparing a photocurable 3D printed transparent conductive hydrogel according to claim 1, characterized in that: In step (1), the ratio of dopamine to pyrrole is (0.1-0.3) g:0.12 mL.
3. The method for preparing a photocurable 3D printed transparent conductive hydrogel according to claim 1, characterized in that: In step (1), the preparation process of the mixed solution specifically includes: dissolving dopamine powder in a first acid solution in an ice water bath at 0 to 10° C., adding pyrrole, and stirring at a speed of 50 to 200 rpm to completely dissolve the pyrrole to obtain a mixed solution; The first acid solution includes a hydrochloric acid solution with a concentration of 0.5 to 3 mol / L; the ratio between the dopamine and the first acid solution is (0.025 to 0.3) g: 20 mL.
4. The method for preparing a light-cured 3D printed transparent conductive hydrogel according to claim 1, characterized in that: In step (1), the mass ratio of dopamine to oxidant is (0.025-0.3): (0.2-0.5); The oxidant solution is an acidified ferric salt solution; the acidified ferric salt solution is obtained by dispersing an iron salt in a second acid solution; the iron salt includes anhydrous ferric chloride, and the second acid solution includes a hydrochloric acid solution with a concentration of 0.5 to 3 mol / L; the ratio between the iron salt and the second acid solution is (0.2 to 0.6) g: 5 mL; The reaction is stirred in an ice-water bath at 0-10°C for 9-12 hours.
5. The method for preparing a light-cured 3D printed transparent conductive hydrogel according to claim 1, characterized in that: In step (2), the concentration of PDA-PPY in the dispersion is 0.1 to 0.6 mg / mL; The decomposition promoting agent includes ammonium persulfate; the mass ratio of PDA-PPY powder to the decomposition promoting agent is 1: (10-30); The reaction conditions after adding the decomposition promoting agent in step (2) are: stirring at a rotation speed of 50 to 200 rpm for 10 to 24 hours.
6. The method for preparing a photocurable 3D printed transparent conductive hydrogel according to claim 1, characterized in that: In step (3), the preparation steps of the methacrylated gelatin include: Gelatin is dissolved in 0.2-0.3 mol / L carbonate buffer, methacrylic anhydride is added dropwise to react, the pH value of the reaction solution is adjusted to 7.2-7.8 to stop the reaction, and finally methacrylic acid acylated gelatin is obtained by dialysis and drying; wherein the ratio between gelatin and carbonate buffer is (15-25) g: 200 mL; the ratio between gelatin and methacrylic anhydride is (15-25) g: 2 mL; The grafting rate of methacrylic anhydride of the methacrylated gelatin is 70 to 90%.
7. The method for preparing a light-cured 3D printed transparent conductive hydrogel according to claim 1, characterized in that: In step (3), the ratio of the methacrylated gelatin to the decomposition solution of PDA-PPY is (0.1-0.5) mg:1 mL.
8. The method for preparing a light-cured 3D printed transparent conductive hydrogel according to claim 1, characterized in that: In step (3), the mass ratio of the methacrylated gelatin to the photocrosslinking agent is (1-5):100; The photocrosslinking agent includes lithium phenyl-2,4,6-trimethylbenzoylphosphinate or 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone; The dissolution conditions of methacrylated gelatin are: stirring at 35-45° C. and 50-200 rpm for 1-2 hours; the mixing conditions after adding the photocrosslinking agent are: stirring at 35-45° C. and 0.5-2 hours.
9. The method for preparing a light-cured 3D printed transparent conductive hydrogel according to claim 1, characterized in that: In step (3), the 3D printing conditions include: a printing speed of 6 to 10 mm / s, a printing pressure of 0.15 to 0.25 MPa, a printing spacing of 0.5 to 1.8 mm, and a barrel temperature of 10 to 18°C; The conditions for light curing include: UV curing.
10. The photocurable 3D printed transparent conductive hydrogel prepared by the preparation method according to any one of claims 1 to 9.